MicroRNAs: tiny players with a big role in the pathogenesis of leukemias and lymphomas - Francesca Fanini; Ivan Vannini; Muller Fabbri (Hematology Reports, 2009)
MicroRNAs (miRNAs) are small non-coding RNAs (ncRNAs) with important regulatory functions. After an initial phase, aimed at identifying whether a deregulation in miRNA expression occurred between hematologic malignancies and their normal counterparts, currently an increasing number of studies are focusing on the functional significance of these aberrancies. The identification of miRNA targeted genes has cast a new light on the role of these tiny ncRNAs in human cancerogenesis, providing a new rationale to the observed diagnostic, prognostic and therapeutic implications of miRNA aberrant expression in human hematologic malignancies.